Theoretical Study of the Stereodynamics of the Reactions of Ne + H2+ ® NeH+ + H and Ne + D2+ ® NeD+ + D - Wang, Yuliang; Qu, Liangsheng; Jiang, Yanlan; Chen, Juna (Asian Journal of Chemistry, 2012)
Based on the adiabatic potential energy surface of the ground state l2A’ constructed by Lv et al. The probabilities of the reactions Ne + H(D)2+ ® NeH(D)+ + H(D) for J = 0 have been calculated by the quasiclassical trajectory method. Comparing the dynamics of Ne + D2+ ® NeD+ + D with Ne + H2+ ® NeH+ + H, the four generalized polarization dependent differential crosssections (PDDCSs) (2p/s)(ds00/dwt), (2p/s)(ds20/dwt), (2p/s)(ds22+/dwt), (2p/s)(ds21−/dwt) have been calculated in the centre of mass frame, respectively. The P(qr), P(fr) and P(qr, fr) distributions, the k-k’-j’ correlation and the angular distribution of product rotational vectors are presented in the form of polar plots. A pronounced isotope effect on the product polarization is also revealed. This effect may be derived from the different mass factor or the effective potential well depth in the two reactions.